PENGARUH KOMPETENSI GURU ABK PADA INDIKATOR PENILAIAN DI SEKOLAH INKLUSI MADRASAH IBTIDAIYAH AR-ROIHAN LAWANG - Tities Hijratur Rahmah (Paradigma: Jurnal Filsafat, Sains, Teknologi, dan Sosial Budaya, 2017)
The focus of this analysis is to know the effect of the teacher’s competence toward teacher’s indicator value.The population of this Research is the teacher in Madrasah Ibtidaiyah Terpadu Ar-Roihan Lawang. In conducting this research, the researcher used correlational quantitative research. With the total of the sample are 37 teachers and using simple linear regression technique. The result of the analysis shows that the correlation coefficient value R = 0,596 and included medium category. In the “ANOVA”computation, the value of Regression Sig obtained 0.000 and <0.05 then concluded “There is a significant influence between the competence of teachers shadow (X) on assessment indicators (Y)”.